O ewolucji wyobrażeń i praktyki w zakresie prowadzenia dzienniczka uczącego się. Refleksje nad wynikami badania własnego - Wiater, Aleksander (Neofilolog, 2024)
Among the foreign language learning strategies classified by R. Oxford (1990) as indirect are affective strategies, to which the researcher assigns an important role in regulating the process of acquiring knowledge and skills. One of the basic tools used for this purpose is a diary, which helps a learner identify their feelings, attitudes and motivations related to language learning. It can be kept both in the form of individual notes on paper or through electronic entries on a group forum, including interactive exchange of reflections. The change in the formula makes it not only a personal record, but also a testimony of various cognitive experiences that we share with others. The aim of the article is to present the changes taking place in the chosen form of the diary, which becomes not only a place for reflection, but also for the exchange of learning experiences, including metacognitive and social strategies. The research conducted in the period from the academic year 2018/19 to 2022/2023 covered five classes of first-year students of French Philology at the University of Wrocław and was aimed at examining preferences in relation to an open or closed form of keeping a diary of the learning strategies used. During the longitudinal research, statements from learners were collected (207 questionnaires), which pointed out the advantages and disadvantages of both forms of diary and commented on the usefulness of the tool in reflection on learning strategies used in practice.